Enriched support for ring constraints - Halpin, Terry (Springer Berlin Heidelberg, 2011)
Fact-oriented modeling approaches such as Object-Role Modeling (ORM) have long supported several varieties of ring constraints, such as irreflexivity, asymmetry, intransitivity, and acyclicity, on pairs of compatible roles. The latest version of the Web Ontology Language (OWL 2) supports five kinds of ring constraint on binary predicates. Recently, three more ring constraint types (local reflexivity, strong intransitivity, and transitivity) were added to ORM. This paper discusses these new additions to ORM, as implemented in the Natural ORM Architect (NORMA) tool, and identifies important ways in which ORM and OWL differ in their support for ring constraints, while noting different mapping alternatives. We determine which combinations of elements from this expanded set of ring constraints are permitted, and provide verbalization patterns for the new additions. Graphical shapes for the new constraints and constraint combinations are introduced and motivated, and NORMA’s new user interface for entry of ring constraints is illustrated.